Clinical analysis of patients with central nervous system metastases from breast cancer - Gottwald, Leszek; Spych, Michał; Moszyńska-Zielińska, Małgorzata; Misiewicz, Piotr; Dukowicz, Andrzej; Bibik, Robert; Serbiak, Beata; Fijuth, Jacek (Menopause Review/Przegląd Menopauzalny, 2012)
Background : Breast cancer is the most common malignant neoplasm in women. Metastases to the central nervous system (CNS) are diagnosed in 15% of metastatic diseases. Aim of the study: The aim of the study was to investigate the clinical features in patients with breast cancer metastasized to the CNS. Material and methods : 54 patients were studied retrospectively. Clinical and pathologic data were analyzed. The time from primary diagnosis to relapse in the CNS was evaluated. The CNS tumors were characterized. Results : At the diagnosis of primary cancer, patients were aged 34-87 (54.8 ±10.0). The histology was ductal adenocarcinoma (88.9%) and lobular adenocarcinoma (11.1%). The interval from diagnosis of primary cancer to the CNS relapse was 2-96 months (35.6 ±23.8). The CNS metastases were less often solitary (27.8%) than multifocal (72.2%). 25.9% of metastatic tumors were diagnosed only in the CNS, and 74.1% of patients had extracranial metastases. The synchronous metastases were located most commonly in the lungs, liver, bones, and the lymphatic system. The treatment of relapse in the brain was in 25.9% - the surgery followed by radiotherapy, in 61.1% of patients - radiotherapy alone, in 3.7% - radiotherapy followed by chemotherapy and in 9.3% - palliative care only. Conclusions : The development of the CNS metastases from breast cancer occurs commonly in patients with an inoperable primary tumor, 2-3 years after primary diagnosis. The tumors are usually multiple and are diagnosed in patients with synchronous extracranial metastases. The development of the CNS metastases, despite oncologic treatment, is related to poor prognosis and most patients die during the first year of the follow-up.